SOSIALISASI PENINGKATAN KUALITAS PRODUKTIVITAS PANEN UDANG MELALUI PENGONTROLAN KADAR AIR BERBASIS IOT DI DESA KUALA CEURAPE - Nunsina, Nunsina; Zuhra, Fatimah; Yunizar, Zara (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Pond water quality is the main factor for the survival and productivity of shrimp farming. Physical parameters such as temperature, salinity and water turbidity are the main indicators of pond water quality. Poor water quality can reduce appetite, growth rate, and increase the risk of disease in shrimp. To overcome this problem, an effective monitoring and control system is needed. The method used in implementing this community service activity covering observation, design and socialization of the use of IoT-based automatic water content control devices. The results showed that the device is effective in helping fishermen controlling water levels automatically, increasing efficiency and effectiveness. The technology used includes the Arduino Uno microcontroller, ultrasonic sensor, RTC, LCD, relay module, motor driver, and DC motor. This activity is expected to provide new knowledge for fishermen in increasing shrimp productivity and quality through automatic control of pond water.